ANALISIS PENELUSURAN MASKER SEBAGAI PROTOKOL KESEHATAN SAAT PANDEMI COVID-19 DI INDONESIA: STUDI GOOGLE TRENDS - Ully Febra Kusuma; Nurunnisa Arsyad; Melissa Shalimar Lavinia; Selvia Rahayu; Muhammad Khairul Kahfi Pasaribu; Rizma Adlia Syakurah (Dian Nuswantoro Semarang, 2021)
AbstrakMedical masks are also used by people at risk who are indicated to need them. The supply of medical masks is limited, the general public is encouraged to use non-medical masks or cloth masks. This article will discuss the comparison of search results for sensi masks, cloth masks and N-95 masks using google trend analysis. This research method is a qualitative and quantitative study using time series data with quantitative analysis, time-lag correlation is used to assess whether an increase in GT data is correlated with an increase in COVID-19 cases. Data from google trends regarding keywords related to one of the preventive measures for COVID-19, namely masks such as